Comparative analysis of boar seminal plasma proteome from different freezability ejaculates and identification of Fibronectin 1 as sperm freezability marker. (9th February 2015) - Vilagran, I.; Yeste, M.; Sancho, S.; Castillo, J.; Oliva, R.; Bonet, S.
Summary: Variation in boar sperm freezability (i.e. capacity to withstand cryopreservation) between ejaculates is a limitation largely reported in the literature. Prediction of sperm freezability and classification of boar ejaculates into good (GFEs) and poor freezability ejaculates (PFEs) before cryopreservation takes place may increase the use of frozen‐thawed spermatozoa. While markers of boar sperm freezability have been found from sperm cell extracts, little attention has been paid to seminal plasma. On this basis, the present study compared the fresh seminal plasma proteome of 9 GFEs and 9 PFEs through two‐dimensional difference gel electrophoresis (2D‐DIGE) and liquid chromatography mass spectrometry (LC‐MS/MS). The ejaculates were previously classified as GFE or PFE upon their sperm viability and progressive motility assessments at 30 and 240 min post thawing. From a total of 51 spots, four were found to significantly ( p  <   0.05) differ between GFEs and PFEs, and two were identified as fibronectin‐1 (FN1) and glutathione peroxidase 5 (GPX5). These two potential markers were further studied by western blot and correlation analysis between protein relative abundances in fresh seminal plasma and regression factors from principal component analyses (PCA) run using post‐thawing sperm quality parameters. Results confirmed that FN1 is a reliable marker of boar sperm freezability, because GFEs presented significantly ( p  <   0.05) higher FN1‐amounts than PFEs and FN1 was found to be correlated with the first PCA component at 240 min post thawing. In contrast, GPX5 was not validated as a boar sperm freezability marker. We can thus conclude that levels of FN1 in fresh seminal plasma from boar semen may be used as a sperm freezability marker, thereby facilitating the use of frozen‐thawed boar spermatozoa.